2008
DOI: 10.1099/vir.0.83339-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of potential risks associated with recombination in transgenic plants expressing viral sequences

Abstract: Virus-resistant transgenic plants have been created primarily through the expression of viral sequences. It has been hypothesized that recombination between the viral transgene mRNA and the RNA of an infecting virus could generate novel viruses. As mRNA/viral RNA recombination can occur in virus-resistant transgenic plants, the key to testing this risk hypothesis is to compare the populations of recombinant viruses generated in transgenic and non-transgenic plants. This has been done with two cucumoviral syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 27 publications
0
25
1
Order By: Relevance
“…The 39-NCR can serve as an initiation site for the viral replicase (Teycheney et al, 2000), thus making it possible for full-length recombinant RNA3 that can potentially be replicated to be produced by a single crossover. Turturo et al (2008) showed clearly that the populations of recombinant viral RNAs were similar in the transgenic plant system when infected with a subgroup I CMV (I17F-CMV) and in the non-transgenic plants infected simultaneously with both CMV strains. However, the populations were, in both cases, completely dominated by recombinants at a single hotspot.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…The 39-NCR can serve as an initiation site for the viral replicase (Teycheney et al, 2000), thus making it possible for full-length recombinant RNA3 that can potentially be replicated to be produced by a single crossover. Turturo et al (2008) showed clearly that the populations of recombinant viral RNAs were similar in the transgenic plant system when infected with a subgroup I CMV (I17F-CMV) and in the non-transgenic plants infected simultaneously with both CMV strains. However, the populations were, in both cases, completely dominated by recombinants at a single hotspot.…”
Section: Introductionmentioning
confidence: 98%
“…Tobacco (Nicotiana tabacum Xanthi XHFD8) plants were maintained in greenhouse conditions of 25±2 uC and 75±10 % relative humidity with a 16 h day length. Transgenic line 40.5 expresses the CP and entire 39-NCR of R-CMV RNA3 (subgroup II) (Turturo et al, 2008), and is not resistant to I17F-CMV (subgroup I). Cloned cDNAs of RNAs 1, 2 and 3 (pI1T7, pI2T7 and pI3T7, respectively) of I17F-CMV (Jacquemond & Lot, 1981) (kindly provided by M. Jacquemond, INRA, Avignon, France) were linearized and plants were inoculated as described previously .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes studies such as those described in the previous section in the area of the impact of modified fitness of crops and crop relatives, but generic research can be equally important in other areas to GMO risk assessment. For instance, it took nearly 10 years to come to a point of completion regarding the potential impact of recombination in virus-resistant transgenic plants (Aaziz and Tepfer, 1999;de Wispelaere et al, 2005;Turturo et al, 2008). …”
Section: Conclusion and Recommendationsmentioning
confidence: 99%